Science policy vs. technology policy - Szanto, Borisz
The author suggests that at present science policy and technology policy tend to be viewed as achieving the same end in gaining technological advantage. He argues the desirability of separating these two policies and defining their individual aims clearly.
On the higher stage of cognitive evolution, the concept of innovation management shifts toward a strategic design of the conscious socio-technical evolutionary movement. The paper investigates the question of why on this higher stage of human development, conventional science policy confronts engineering concept of technology development? Also, why, despite this, are science and technology policy one in its intention? The concept of a new alliance between science, technology and society is urged, on the grounds that the model of development we use in Europe still contemplates both science and technology as endogenous factors of economy, which they are not. The paper raises the question of whether, on the higher stage of socio-technical evolution, the scientific and technological advances can really be taken as inner resources of economic development, with production of knowledge as a function of capital accumulation. It is argued that either on a corporate or on a government level, the matter of an engineering approach to creation and the implementation of technological advantage, and the matter of scientific cognition should be conceptually the same in intention, but separated in accomplishment, because of their different directions. The concept of science and technology policy ought to be reconsidered and separated accordingly.
Keywords: Science policy; Technology policy